Carbon Stock and Some Chemical Properties of Soil in Sacred Groves and Pollarded Forest Stands of Northern Zagros Forests - Niloofar Koosha; Kyumars Mohammadi Samani; Vahid Hosseini (مجله آب و خاک, 2022)
IntroductionA large part of forest and woodland ecosystems in Iran have been located in arid and semi-arid areas which low level of soil organic carbon (SOC) is considered as one of the main problems. Millions of trees together that make forest ecosystems, play a major role in carbon sequestration and can sequester it in the form of biomass, above ground in plants and also underground in plants root or in the soil. Forest ecosystems play a significant role in absorbing and reducing greenhouse gases and therefore, can play a crucial role in decreasing global warming. Soil is one of the great sources of carbon storage, which plays a significant role in the atmospheric carbon deposition and dioxide gas. The carbon stored in the soil changes under some important driving factors such as: land use change, animal grazing, pollarding, exploitation (included forest harvesting), topography and forest trees, and types. One of the main sources of income for forest stakeholders in Zagros area is the Zagros oak forest. These people livelihoods are heavily dependent on natural resources, especially forest, known as a kind of traditional land use system called “Galazani”. Each family, in this system, has its own common ownership and manages their proprietorships called “Gallajar” which is a part of the woodlands and use some kind of traditional silvopastoral techniques to use these areas. Dominant livestock in the most part of theses area are goats and sheep. In the growing season, they usually feed on ground vegetation and in the winter time, they use dried oak leaves (leaf hay) that is stored before on some special trees call “Daar-Galla”. In the northern part of Zagros oak forest (Kurdistan province), there are some very special stands that are found around every village called sacred groves and are totally intact because of some spiritual values and taboos. There are no exploitation and grazing and even land use changing in these areas, and they show the real undisturbed forest lands in Zagros. The aim of this research was to study and compare soil carbon stock and some essential soil properties in sacred groves and pollarded forests (Gallajar) of northern Zagros forests in order to obtain more precise data in soil after high exploitation and pollarding.Materials and MethodsThe average annual rainfall in 25 recent years in the study is 690 mm and the average annual temperature is 14.2 degrees Celsius. The dominant trees species in the region are Lebanon oak, Aleppo oak and Persian oak. To conduct this investigation, three study areas included both sacred groves and Gallajars, in three main slope aspects including north, east and south facing aspects, were chosen. Then six plots (10 a) were randomly selected in each area and tree canopy (%) and litter percentage were determined in the field. Soil samples took in two depths (0-15 and 15-30 cm) in the center of each plots and then bulk density (BD) and some chemical soil properties included soil organic carbon, soil carbon stock, total nitrogen (N), phosphorus (P), potassium (K), electrical conductivity (EC) and pH were measured in the soil laboratory. A factorial randomized complete block design was used to analysis soil data.Results and DiscussionThe results showed that there were significant differences between soil depths for studied soil properties except BD, N and K and also there were significant differences in various slope aspects in studied parameters. However, no such a trend was observed in soil N and EC. The results also revealed that pollarding had significant effects on all studied soil properties. In addition, all studied soil properties including SOC stock, N, P, K and EC in sacred groves was higher than Gallajars while pH and BD were increased in pollarded areas. The amount of SOC stock, N, P and EC were greater at depth 0-15 compared to depth of 0-15 cm while, pH showed lower amount in the surface soil layer and K and BD had no significant differences in the two studied soil layers. SOC stock in northern, eastern and southern slope aspect were 72.6, 48.2 and 45 tons/ha, respectively. Pollarding and livestock grazing in Gallajars caused a significant decrease in tree canopy and, as a result, the litters on the grounds also reduced. Therefore, it seems that the reduction of trees and canopy cover affected soil properties significantly and reduced SOC stock meaningfully in the long term. Other essential chemical soil properties were also lower in Galajars compared to sacred groves.ConclusionFinally, we can claim that, some factors including pollarding and grazing can significantly reduce SOC stock and other studied soil properties in this research. On the one hand, people are using these forest areas as grazing pastures and also for pollarding trees to fed their livestock and the government could not have convinced them not to pollard the trees and, on the other hand, the results in this study showed that these pollarding operations are affecting forest stands and forest soil chemical properties and SOC stock significantly and reduce their quality considerably. It can be suggested that some new management treatments should be done in these forest areas through the training of local people, preparing sufficient fodder resources and providing enough facilities by the government to reduce pollarding by stakeholders. As a result, the natural process of production and decomposition of organic matter may be controlled in a better way, so that, the soil quality and carbon storage in these forests to be improved in the long term.